2021
DOI: 10.1097/qai.0000000000002642
|View full text |Cite
|
Sign up to set email alerts
|

Brief Report: Switching to DOR/3TC/TDF Maintains HIV-1 Virologic Suppression Through Week 144 in the DRIVE-SHIFT Trial

Abstract: Supplemental Digital Content is Available in the Text.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
33
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(35 citation statements)
references
References 17 publications
2
33
0
Order By: Relevance
“…DOR has not been studied in the setting of resistance mutations; clinical trials have compared this new NNRTI with boosted darunavir (bDRV) and efavirenz (EFV) in naive setting, [ 6 , 7 , 12 ] and have also explored its role in switching strategies. [ 8 , 13 ]…”
Section: Introductionmentioning
confidence: 99%
“…DOR has not been studied in the setting of resistance mutations; clinical trials have compared this new NNRTI with boosted darunavir (bDRV) and efavirenz (EFV) in naive setting, [ 6 , 7 , 12 ] and have also explored its role in switching strategies. [ 8 , 13 ]…”
Section: Introductionmentioning
confidence: 99%
“…Results from clinical trials confirmed a good safety profile of DOR both on HIV virological control and on metabolic profile. [ 3 4 5 ] Moreover, when compared with other agents of the same class, DOR seems to have a better tolerability profile, less interactions with food or drugs, and a higher genetic barrier. [6] …”
Section: Introductionmentioning
confidence: 99%
“…We read with interest the recently published results from the DRIVE-SHIFT trial, 1 whose results confirm the efficacy and safety of doravirine (DOR), in association with a 2-nucleoside reverse transcriptase inhibitor (NRTI) backbone, in virologically suppressed people living with HIV (PLWHIV). However, as we have learned in the past, results from clinical trials do not always translate directly to the “real-life” setting.…”
mentioning
confidence: 99%